Dentistry as a cause of Endocarditis in Baghdad governorate (Mustansiria Dental Journal, 2018)
Endocarditis is a localized microbial infection of the heart valves or endocardium adjacent to congenital or acquired heart defects. It is the dentist's responsibility to prevent the occurrence of endocarditis by following the latest recommendations usually issued by the American Heart Association on prevention of endocarditis. The purpose of this investigation was to determine the role of Dentistry in causing endocarditis among Iraqi at risk patients. A retrospective study of patient's records in three major hospitals in Baghdad was done. Thirty three cases of bacterial endocarditis were found and examined .The results indicated that (18%) of cases were preceded by dental procedures. Compliance with the guidelines on prevention of endocarditis is necessary for all at risk patients.